HUROOF E TEHJI : SMART FLASH CARDS - Shama Zain (PARAMOUNT BOOKS)
Smart Flash Cards Huroof e Tehji is an interactive series of 11 sets, ideal for children$1 (Bs early learning at school or home. The flashcards encourage learning and recognizing the alphabet, huroof-e-tahajji, phonics, and numbers with age-appropriate vocabulary and engaging pictures. The series comprises all the topics necessary to equip children with early-level education and build their language skills for day-to-day use. It has 32 durable flash cards with wipe-clean activities in some sets, including a marker, to reinforce learning, develop hand-eye coordination, and improve visual recognition.s